2006
DOI: 10.1086/501430
|View full text |Cite
|
Sign up to set email alerts
|

The Dwarf Novae during Quiescence

Abstract: We present a synthetic spectral analysis of nearly the entire far ultraviolet IUE archive of spectra of dwarf novae in or near their quiescence. We have examined all of the systems for which the signal to noise ratio permitted an analysis. The study includes 53 systems of all dwarf nova subtypes both above and below the period gap. The spectra were uniformly analyzed using synthetic spectral codes for optically thick accretion disks and stellar photospheres along with the bestavailable distance measurements or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 69 publications
3
36
1
Order By: Relevance
“…Therefore, only a lower limit to the distance can be obtained by using this method due to the effects of the disc and the irradiated area of the secondary star (Berriman, Szkody & Capps 1985). Almost all distance estimation methods attempts to use properties of a component of the system such as surface brightness of the secondary star (Bailey 1981), spectra of the white dwarf (Sion et al 1995;Urban & Sion 2006) and M V − P orb relationship of dwarf novae at outburst (Warner 1995;Harrison et al 2004). However, none of them can give a distance as precise as trigonometric parallax due to the contaminations from the other components and the lack of the information about the individual contributions of the components to the observed light.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, only a lower limit to the distance can be obtained by using this method due to the effects of the disc and the irradiated area of the secondary star (Berriman, Szkody & Capps 1985). Almost all distance estimation methods attempts to use properties of a component of the system such as surface brightness of the secondary star (Bailey 1981), spectra of the white dwarf (Sion et al 1995;Urban & Sion 2006) and M V − P orb relationship of dwarf novae at outburst (Warner 1995;Harrison et al 2004). However, none of them can give a distance as precise as trigonometric parallax due to the contaminations from the other components and the lack of the information about the individual contributions of the components to the observed light.…”
Section: Introductionmentioning
confidence: 99%
“…Urban & Sion 2006;Townsley & Gänsicke 2009) -by comparison the well-studied dwarf nova U Gem has overall properties which are very similar to SDSS J1006 but harbours a WD with T WD ≈ 30 000 K (Sion et al 1998;Long et al 2006). Given that SDSS J1006 is a high-inclination system, it might be possible that the WD is partially veiled by extended structures above the accretion disc, similar to those seen in OY Car (Horne et al 1994).…”
Section: Distance and White Dwarf Temperaturementioning
confidence: 85%
“…Perhaps the least understood topic in cataclysmic variable (CV )/ DN research (along with what drives the wind outflow in outburst) is the state and structure of the boundary layer and accretion disk during quiescence and the physics of how the long-term accretion of mass, angular momentum, and energy affects the WD. Our studies with archival IUE data and Hubble Space Telescope (HST ) STIS have found that $50% of the DNe in quiescence are dominated (i.e., >60% of UV flux) by a component of FUV flux other than the WD called the ''accretion disk''; $25% are dominated by the WD, and $25% have nearly equal contributions of WD and accretion disk (40%Y60% each) ( Urban & Sion 2006).…”
Section: Introductionmentioning
confidence: 84%
“…A number of studies (Araujo-Betancor et al 2003;Sion 1991;Sion 1999;Urban & Sion 2006) have shown that CV WDs above the gap are typically on-average 10,000 K hotter than CV WDs below the period gap (almost certainly a consequence of higher time-averaged accretion rates of systems above the gap but possibly with system total age also being a factor). Since the WD surface temperature is crucial for understanding CV evolution and whether CVs evolve across the period gap, the use of cooling ages and long-term evolutionary model sequences with accretion (including the effects of nova explosions; Townsley & Bildsten 2003) must rely on the empirical WD temperature of the photosphere in equilibrium with long-term compressional heating from accretion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation